Numerical simulation of Joule Thomson effect due to leakage of gases from cracks in a pressure vessel - Poon, Wenwei. (2013)
Compressed Natural Gas (CNG) marine transportation is poised to be a viable solution to bring natural gas supplies to new markets or provide a solution for monetizing stranded gas. However, transporting CNG can be dangerous when there is a leakage of from cracks. The leak may cause a change in the material properties of the pressure vessel containing the gas, hence the crack will propagate and resulting in catastrophic failure.